Respuesta :

Azufre

Answer:

(0,6) and (1.2 , 0)

Step-by-step explanation:

5x + y = 6

if we take x=0

5(0) + y = 6

y = 6            ; so, one of the solution is (0,6)

if we take y=0

5x + (0) = 6

5x = 6

x = 6/5 = 1.2     ; so, the other solution is (1.2 , 0)

But basically, you can find other solutions of the equation if you do this:

5x + y = 6

5x = (6 - y)

x = (6 - y) / 5    ; so if you use whatever number of y, you will find the rigth solution for x.

and you can do the opposite too:

5x + y = 6

y = 6 -5x       ; with this, you can use whatever number of x, and find the right y.

I hope this helps you!!!